Watershed Continuum Monitoring Approach: combining multiple water quality patterns along stream and river flowpaths to track sources, pathways, and processing of pollutants - Sujay S. Kaushal; Ashley E. Mon; Stanley B. Grant; Paul M. Mayer; Aaron J. Porter; Andrew J. Sekellick; Jason H. Chase; Shantanu V. Bhide; John D. Jastram; Tamara A. Newcomer-Johnson; Sydney A. Shelton; Alexis M. Yaculak; et al. (Ecological Engineering, 2026)

Genetic variation and race structure in the tan spot wheat pathogen Pyrenophora tritici-repentis: a microscale assessment in a wheat field of Western Australia - Pao Theen See; Catherine F. Cupitt; Dion Bennett; Caroline S. Moffat; Simon R. Ellwood (Australasian Plant Pathology, 2026)
Population genetics are routinely studied over vast geographical areas to address questions of origin, routes of migration and epidemiology. However, genetic diversity of certain microorganisms such as plant pathogenic fungi are difficult to study even on a small geographical scale due to their mixed reproduction systems, variable population sizes, clonality and versatility to host adaptation. The genetic variation of an economically important wheat fungal pathogen, Pyrenophora tritici-repentis (Ptr), was studied with isolates collected from a naturally infected wheat field located in Western Australia, using microsatellite (SSR) markers. Out of 142 Ptr isolates, 89 individuals showed unique multilocus haplotypes. On single leaves, individual disease lesions mostly consisted of genetically variable Ptr isolates, with very few clonal isolates. Distribution analysis of these indicated that wind-dispersal of Ptr conidia occurred over a small scale within individual leaves as well as longer dispersions of up to 45 m. Race evaluation of the population via effector gene PCR assays defined 136 isolates as race 1 and six as race 2, and there was no indication of genetic groupings based on micro-locations or race. Population structure analysis suggests that the population consists of mixed migrants from long wind-dispersal or field management activities. Nucleotide sequence analysis of the homothallic mating-type genes, MAT1-1 and MAT1-2 revealed sequence conservation within the population. Altogether, the microscale evaluation of the single wheat field isolates demonstrated that the population is suitable for disease screening as it is representative of the wider Ptr population demographic in Australia.

Prenatal exposure to gas stoves, mold, and water damage: Associations with gestational duration and fetal growth in the ECHO cohort - Jiwon Oh; Lesliam Quirós-Alcalá; Mohamad Burjak; Anna J. Ross; Lisa A. Croen; Aisha S. Dickerson; Assiamira Ferrara; Rima Habre; Irva Hertz-Picciotto; Margaret R. Karagas; Christine T. Loftus; Rebecca J. Schmidt; et al. (Environmental Pollution, 2026)

Assessing Potential Data Sources for Landscape-scale Terrestrial Biodiversity Indicators - Tom Bradfer-Lawrence; Meriel Harrison; Adham Ashton-Butt; Sophie Bennett; Robin J. Boyd; Ella Browning; Graeme Buchanan; Adam Fraser; Sian E. Green; Robert Hawkes; Becky E. Heath; Pen-Yuan Hsing; et al. (Environmental Management, 2026)

Lung cancer risk in relation to indicative radon atlas metrics in Northern Ireland: a population-based case–control study using secondary data - Claire M. Delargy; Helen G. Coleman; Quentin G. Crowley; Damien Bennett; Javier Elio; Deirdre Fitzpatrick; Helen Mitchell; Sara M. Wallace; Rawan A. N. Alhattab; Angela Scott; Bernadette McGuinness; Ruth F. Hunter; et al. (Environmental Geochemistry and Health, 2026)
Radon is an established lung carcinogen, but more research is needed to inform whether area-based measures of radon exposure reflect underlying cancer risk. This study, the first of its kind in the UK, aimed to investigate the association between a nationwide indicative radon atlas and lung cancer risk in Northern Ireland, a region in which lung cancer screening programmes are under design. A population-based case–control study was conducted. Primary lung cancer cases ( n = 1,687) from the Northern Ireland Cancer Registry diagnosed in 2006 and 2014 were compared with 8,094 non-lung cancer controls from a large cohort. Radon exposure data were extracted from the Indicative Atlas of Radon, which categorises 1 km 2 areas by the percentage of households exceeding 200 Bq/m 3 . Exposure data were linked to participants by postcode. Logistic regression models adjusted for age, sex, smoking status, deprivation and PM 2.5 exposure were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for lung cancer. Individuals residing in high radon exposure areas (Atlas Class 6) had a greater than two-fold lung cancer risk (adjusted OR: 2.24, 95% CI: 1.25, 3.92) compared to residents in all other areas. This association was revealed after adjusting for PM 2.5 . This study supports the utility of an indicative radon atlas in reflecting underlying population lung cancer risk associated with radon, while highlighting constraints inherent to atlas-based exposure classification and secondary data.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Fertility classification of the cow and peri-estrus sex-steroid hormones is associated with endometrial epithelial cell responses to conceptus and inflammatory signals - Cecilia Constantino Rocha; Mariangela Bueno Cordeiro Maldonado; Fernando S. Mesquita; Alexandra Bennett; Abdul Waheed; Graciana R. Mendina; Gabriela Lomba Dasqueve; Felipe A. C. C. Silva; Marcelo Fábio Gouveia Nogueira; Alan D. Ealy; Thomas Hansen; Mario Binelli (Cell and Tissue Research, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Spatial and temporal variations in the distribution of eastern Australian post-orogenic granites and related mineral deposits: metallogenic and tectonic significance - D. L. Huston; Y. Cheng; S. L. Jones; D. C. Champion; M. D. Norman; M. W. Agnew; A. Cross; V. C. Bennett; R. A. Creaser (Australian Journal of Earth Sciences, 2026)

The 4E-BPs as Translational Regulators in Neurological Disorders: Molecular Mechanisms and Therapeutic Potential - Sindhu S. Baskarapantula; Venkata Surya Kumar; Priyajit Changdar; Debashree Chakraborty; Yogendra Nayak; Albert R. La Spada; Craig L. Bennett; Somasish G. Dastidar (Molecular Neurobiology, 2026)
Protein translation is essential for maintaining the optimal functioning of the human nervous system. The 4E-Binding proteins (4E-BPs) are central regulators of this process, acting on the initiation factor eIF4E. Three homologs 4E-BP1, 4E-BP2, and 4E-BP3, are differentially expressed, with the phosphorylation state controlling cap-dependent translation in response to diverse physiological inputs, including growth factors, cytokines, hormones, nutrient availability, and signaling cascades converging on kinases such as mTOR. Dysregulation of 4E-BP activity has been implicated in multiple disease contexts, including neurodegenerative disorders (e.g., Parkinson’s disease, Alzheimer’s disease), neurodevelopmental disorders (e.g., Autism spectrum disorder, Epilepsy), neuropsychiatric conditions (e.g., Depression, Schizophrenia), and autoimmune diseases (e.g., Multiple sclerosis, Guillain–Barré syndrome). We aim to explore the importance of 4E-BPs through a neurological perspective and understand their role as therapeutic targets. In this review, we provide a comprehensive analysis of the three 4E-BP homologs in the central nervous system, emphasizing the CNS-specific dominance of 4E-BP2 and its link to synaptic plasticity and cognitive function. We further examine and provide mechanistic insights into how 4E-BPs contribute to disease pathogenesis, highlighting both shared and disorder-specific features. Finally, we discuss current therapeutic strategies aimed at modulating the mTOR/4E-BP axis, outline the limitations of existing approaches and identify emerging avenues for drug development. Together, these perspectives underscore the potential of 4E-BPs as both therapeutic targets and biomarkers in neurological disease.

High take of mobulid rays in East Java, Indonesia: landing trends and socio-economic context - Betty J. L. Laglbauer; Muhammad G. Salim; Fahmi; Selvia Oktaviyani; Irianies C. Gozali; Firmansyah Tawang; Hasan S. Rizal; Vidlia P. Rosady; Didik Rudianto; Isabel Ender; Jorge M. R. Fontes; Pedro Afonso; et al. (Environmental Biology of Fishes, 2025)

Dissecting resistance mechanisms to Agroathelia rolfsii in peanut (Arachis hypogaea L.) through comparative RNA-Seq profiling of resistant and susceptible genotypes - Pankaj Kumar Verma; Arindam Das; Manisha Ojha; Koushik Ghose; Gunvant B. Patil; Venkateswara R. Sripathi; Rebecca S. Bennett; Naveen Puppala; Madhusudhana R. Janga (Journal of Plant Pathology, 2025)
Stem rot, caused by the fungal pathogen Agroathelia rolfsii , is a devastating disease in peanut ( Arachis hypogaea L.), resulting in substantial global agricultural losses. This study employed RNA sequencing to unravel the molecular mechanisms of resistance by analysing the gene expression profiles of a resistant peanut genotype (Georgia-03 L) and a susceptible genotype (Valencia C) under normal and infected conditions. From the sequencing data, 405.9 million high-quality reads were successfully mapped to the A. hypogaea reference genome, achieving an average mapping rate of 97%. The alignment showed that out of the 67,124 annotated genes in the Tifrunner genome, 49,598 were expressed in at least one sample. In the resistant genotype, key defense-related genes, including receptor-like kinases, NBS-LRR resistance genes, and transcription factors such as MYB and zinc finger proteins, were strongly induced upon infection in G03L. Weighted Gene Co-expression Network Analysis (WGCNA) identified a coexpression gene module which associated with resistance and enriched with the genes involved in oxidative stress response, secondary metabolism, and cell wall reinforcement. In contrast, the susceptible genotype displayed a limited activation of these defense pathways, emphasizing its vulnerability to A. rolfsii . Functional annotation highlighted critical pathways, such as oxidoreductase activity, glutathione metabolism, and peroxidase-mediated responses, as pivotal to the resistance mechanisms. These findings provide valuable insights into the molecular basis of stem rot resistance in peanuts, offering a foundation for breeding or genetic engineering approaches to enhance disease resistance in susceptible cultivars.

Towards identifying the economically optimum sampling density for variable-rate soil constraint management - S. D. Roberton; J. McL. Bennett; C. R. Lobsey; T. F. A. Bishop (Precision Agriculture, 2025)
The investment in soil sampling is often disproportionate to the level of investment for soil amelioration. While advanced geostatistical Digital Soil Mapping (DSM) methods exist to map spatially variable soils, they are rarely used in precision agriculture, due to the increased soil sampling requirement, the cost of which is perceived as prohibitive. Consequently, soil constraints are regularly managed on blanket-rate basis, where a single rate is applied across spatial variable soils. What sampling density is required to deploy these methods in practice, and can an increased investment in soil sampling enable more economically optimised soil amelioration? This paper presents a method to answer this question in Australian broadacre agriculture. The method, which seeks to identify the economically optimum sampling density, is tested on a 100 ha broadacre grain field in Central NSW, Australia. Sampling densities ranging from 0.1 to 3 samples per ha are tested, through observing the accuracy of gypsum recommendations as a practice to treat sodic soils. A status quo Blanket-rate (BR) approach is tested against DSM via the deployment of ordinary kriging to create continuous variable-rate (VR) recommendations. Application errors are assessed both in terms of cost of over-applied product, as well as lost yield potentialy due to under-application. While for this test site, an economically optimum sampling density of 1 core per 5 ha and 1 core per 2 ha for 0–20 cm topsoil management and 0–60 cm profile management was identified, we propose the development Nopt function. Development of this function would allow for optimum sampling investments to be estimated at new sites, in consideration to the inherent site variability and the economic magnitude of soil amelioration. Through development of this function and it’s applied example in this paper, we seek to develop the value proposition for increased soil data collection in Australian Agriculture.

A widely distributed clam, Chama macerophylla, exhibits mixed responses to single and combined warming and acidification stress - Amanda Kirkland; Alanna J. Frick; Haley R. Beaulieu; Mark Granier; Bennett H. Price; John B. Wiley; Kelly S. Boyle; T. Erin Cox (Marine Biology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

An evidence map of research assessing the effects of timber harvesting on water quality, biotic and biodiversity indicators in running waters - D.E.L. Hanna; M. Harper; X. Giroux-Bougard; J.S. Richardson; T. Rytwinski; A. Bachhuber; E.J. Hudgins; S. Karimi; R. Schuster; A.D. Binley; R. Reedman; J.G. Vincent; et al. (Forest Ecology and Management, 2025)

Prenatal exposure to environmental bisphenols over time and their association with childhood asthma, allergic rhinitis and atopic dermatitis in the ECHO consortium - Rachel L. Miller; Yuyan Wang; Jenny Aalborg; Akram N. Alshawabkeh; Deborah H. Bennett; Carrie V. Breton; Jessie P. Buckley; Dana Dabelea; Anne L. Dunlop; Assiamira Ferrara; Griffith Gao; Abigail Gaylord; et al. (Environmental Pollution, 2025)

Challenges in assessing the effects of environmental governance systems on conservation outcomes - Raphael A. Ayambire; Trina Rytwinski; Jessica J. Taylor; Matthew W. Luizza; Matthew J. Muir; Cynthia Cadet; Derek Armitage; Nathan J. Bennett; Jeremy Brooks; Samantha H. Cheng; Jenny Martinez; Meenakshi Nagendran; et al. (Conservation Biology, 2025)
Effective governance is crucial for the success of conservation projects aimed at protecting wildlife populations and supporting human well‐being. However, few large‐scale, comprehensive syntheses have been conducted on the effects of different environmental governance types on conservation outcomes (i.e., biological and ecological effectiveness or effects of conservation on human well‐being), and clarity on the quantity and quality of evidence remains dispersed and ambiguous. We attempted a systematic map of the evidence on the effectiveness of different governance types to meet desired conservation outcomes in Africa, Asia, and Latin America. However, early in this effort, we observed a general lack of empirical research on the links between governance and conservation outcomes. To fill observed data gaps in the evidence base, we tried triangulating governance data from alternative sources (Protected Planet database) and pooling evidence from research conducted within the same conservation areas. Limited data were contained in the Protected Planet database, and governance types in conservation areas and landscapes were complex, making it difficult to use these approaches to assign governance types to conservation areas. To illustrate our observations from the failed systematic map attempt, we prepared a rapid evidence map that outlines a subset of the evidence base of articles linking governance types and governance principles with conservation outcomes. Only 3.2% (34 of 1067) of the articles we screened directly related conservation outcomes to governance type, and even fewer related governance principles to conservation outcomes. Based on our findings, we recommend improving the evidence base by supporting empirical research and increasing the availability and quality of governance data in freely accessible databases. These recommendations are critical for enhancing understanding of the role of governance in conservation projects and improving conservation outcomes.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Projected distribution shifts of resident monarch butterflies and consequences for migratory monarchs - Iman Momeni-Dehaghi; Lenore Fahrig; Joseph R. Bennett; Trina Rytwinski; Karen S. Oberhauser; Nancy A. Sheehan; Greg W. Mitchell (Journal for Nature Conservation, 2024)

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Trends in flame retardant levels in upholstered furniture and children's consumer products after regulatory action in California - R. Gill; Q. Wang; S. Takaku-Pugh; E. Lytle; M. Wang; D.H. Bennett; J. Park; M. Petreas (Chemosphere, 2024)

On-orbit calibration and performance of the EMIT imaging spectrometer - David R. Thompson; Robert O. Green; Christine Bradley; Philip G. Brodrick; Natalie Mahowald; Eyal Ben Dor; Matthew Bennett; Michael Bernas; Nimrod Carmon; K. Dana Chadwick; Roger N. Clark; Red Willow Coleman; et al. (Remote Sensing of Environment, 2024)

Structured decision making remains underused in ecological restoration despite opportunities - Morgan L. Piczak; Jessica A. Robichaud; Peter Morrison; Andrew M. Rous; Ingeborg M. Mulder; Cassandra J. Hill; Tanya S. Prystay; Hanna Rosner-Katz; Kelly F. Robinson; Joseph R. Bennett; Steven J. Cooke (Environment Systems and Decisions, 2024)

Sicklefin Chub (Macrhybopsis meeki) and Sturgeon Chub (M. gelida) Temporal and Spatial Patterns from Extant Population Monitoring and Habitat Data Spanning 23 Years - Mark L. Wildhaber; Benjamin M. West; Kendell R. Bennett; Jack H. May; Janice L. Albers; Nicholas S. Green (Fishes, 2024)
Sicklefin (Macrhybopsis meeki) and sturgeon chub (M. gelida) historically occurred throughout the Missouri River (MR), in some tributaries, and Mississippi River downstream of the MR. They have been species of U.S. state-level conservation concern and U.S. Endangered Species Act listing candidates since the 1990s. We applied analytical approaches from occupancy modeling to correlation to monitoring data spanning 23 years to assess relationships between occupancy and time, space, environmental factors, habitat, and other species. Sicklefin chub occupancy appeared higher in the early to mid-2000s and mid-to-late 2010s. A potential decline in occupancy occurred for sturgeon chub in the mid-to-late 2010s. Spatially, chub occupancy was depressed for 159 to 438 km downstream of MR dams. Among macrohabitats, inside bends had relatively high occupancy for both species; secondary connected channels had relatively high values for sturgeon chub. Co-occurrence was likely between sicklefin and sturgeon chub and between chubs and shovelnose sturgeon (Scaphirhybchus platorybchus) and channel catfish (Ictalurus punctatus). The observed co-occurrence of chubs and pallid sturgeon (Scaphirhynchus albus; PS) was potentially higher than expected for adult PS. For juvenile PS, co-occurrence was lower than expected in the Lower MR and potentially higher than expected in the Upper MR, warranting future research. Results from this research suggest management for the improvement of sicklefin and sturgeon chub populations may benefit other MR fish populations.

A horizon scan of global biological conservation issues for 2024 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Stuart H.M. Butchart; Holly M. Butterworth; Stewart J. Clarke; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jennifer James; et al. (Trends in Ecology & Evolution, 2024)

Toxic Tire Wear Compounds (6PPD-Q and 4-ADPA) Detected in Airborne Particulate Matter Along a Highway in Mississippi, USA - Boluwatife S. Olubusoye; James V. Cizdziel; Matthew Bee; Matthew T. Moore; Marco Pineda; Viviane Yargeau; Erin R. Bennett (Bulletin of Environmental Contamination and Toxicology, 2023)

Associations between area-level arsenic exposure and adverse birth outcomes: An Echo-wide cohort analysis - Jonathan V. Lewis; Emily A. Knapp; Shivani Bakre; Aisha S. Dickerson; Theresa M. Bastain; Casper Bendixsen; Deborah H. Bennett; Carlos A. Camargo; Andrea E. Cassidy-Bushrow; Elena Colicino; Viren D’Sa; Dana Dabelea; et al. (Environmental Research, 2023)

The biology of an isolated Mashona mole-rat population from southern Malawi, with implications for the diversity and biogeography of the genus Fukomys - R. Šumbera; M. Uhrová; S. Begall; K. R. Caspar; D. Jerkovičová; P. Van Daele; W. N. Chitaukali; C. G. Faulkes; N. C. Bennett; C. Johannes; H. Burda; O. Mikula (Organisms Diversity & Evolution, 2023)
The Mashona mole-rat, Fukomys darlingi (Thomas, 1895), is a little studied social African mole-rat (Bathyergidae) from south-astern Africa. Here, we present an integrative study characterizing the genetic diversity of populations assigned to F. darlingi with special focus on animals from Nsanje, southern Malawi. These mole-rats show pronounced differences in body mass and general appearance compared to nominate F. darlingi from Zimbabwe and Mozambique, but their taxonomic status has so far remained unclear. A genetic analysis encompassing all major lineages of the genus Fukomys suggests that this population indeed represents a deeply nested lineage within the F. darlingi clade . The karyotype of the Nsanje mole-rats also corresponds to that of the nominate form, being 2n = 54. While both nuclear and mitochondrial data agree about the assignment of the Nsanje mole-rats to F. darlingi , our analyses revealed substantial mitonuclear discordance for other branches within the Fukomys phylogenetic tree. Nsanje mole-rats are significantly larger than nominate F. darlingi and their ontogeny and reproduction closely resemble similar-sized congeneric species rather than the nominate population. The somatic growth of the Nsanje form is the slowest of all African mole-rats. The maximum life span of F. darlingi is at least 19 years. The observed differences between nominate F. darlingi and mole-rats from Nsanje may be attributed mainly to their different body mass. Our study highlights the advantages of an integrative approach for understanding the diversity of African mole-rats and emphasizes the great intraspecific variability that may be encountered in these underground-dwelling rodents.

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

Search for CP violation and measurement of branching fractions and decay asymmetry parameters for Λ c + → Λ h + and Λ c + → Σ 0 h + ( h = K , π ) - L.K. Li; W. Shan; K. Kinoshita; I. Adachi; H. Aihara; D.M. Asner; H. Atmacan; T. Aushev; V. Babu; S. Bahinipati; Sw. Banerjee; P. Behera; et al. (Science Bulletin, 2023)

Polymorphism of the follicle stimulating hormone receptor does not impact reproductive performance or in-vitro embryo production in beef heifers - Alexandria P. Snider; Hannah K. Yake; Camryn D. Granger; Shelby L. Rosasco; Tara G. McDaneld; Warren M. Snelling; Chad C. Chase; Jeremy R. Miles; Clay A. Lents; Lacey K. Quail; Jerica J.J. Rich; Kaitlin M. Epperson; et al. (Theriogenology, 2023)

Rank change and growth within social hierarchies of the orange clownfish, Amphiprion percula - L. M. Fitzgerald; H. B. Harrison; D. J. Coker; P. Sáenz-Agudelo; M. Srinivasan; J. E. Majoris; L. Boström Einarsson; B. Pujol; M. Bennett-Smith; S. R. Thorrold; S. Planes; G. P. Jones; et al. (Marine Biology, 2022)
Social hierarchies within groups define the distribution of resources and provide benefits that support the collective group or favor dominant members. The progression of individuals through social hierarchies is a valuable characteristic for quantifying population dynamics. On coral reefs, some clownfish maintain size-based hierarchical communities where individuals queue through social ranks. The cost of waiting in a lower-ranked position is outweighed by the reduced risk of eviction and mortality. The orange clownfish, Amphiprion percula , maintains stable social groups with subordinate individuals queuing to be part of the dominant breeding pair. Strong association with their host anemone, complex social interactions, and relatively low predation rates make them ideal model organisms to assess changes in group dynamics through time in their natural environment. Here, we investigate the rank changes and isometric growth rates of A. percula from 247 naturally occurring social groups in Kimbe Island, Papua New Guinea (5° 12′ 13.54″ S, 150° 22′ 32.69″ E). We used DNA profiling to assign and track individuals over eight years between 2011 and 2019. Over half of the individuals survived alongside two or three members of their original social group, with twelve breeding pairs persisting over the study period. Half of the surviving individuals increased in rank and experienced double the growth rate of those that maintained their rank. Examining rank change in a wild fish population provides new insights into the complex social hierarchies of reef fishes and their role in social evolution.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Does bait type and bait container configuration influence the performance of remote underwater video systems in temperate freshwater lakes for assessing fish community structure? - D. M. Glassman; A. Chhor; J. C. Vermaire; J. R. Bennett; S. J. Cooke (Hydrobiologia, 2022)

A Multi-Tissue, Multi-Species Assessment of Lipid and Urea Stable Isotope Biases in Mesopredator Elasmobranchs - Joshua Bennett-Williams; Christina Skinner; Alex S. J. Wyatt; Rona A. R. McGill; Trevor J. Willis (Frontiers in Marine Science, 2022)
The application of stable isotope analysis (SIA) is increasing in elasmobranch trophic ecology, but inconsistency remains in terms of the tissue pre-treatment methods chosen to remove biases introduced by lipids and urea. SIA of a range of non-lethally extracted tissues from a diverse group of elasmobranchs, including mesopredators, is increasing, yet most studies assume that isotope biases from lipid and urea are the same across tissues and species. To determine tissue- and species-specific isotope biases across treatment methods, three tissues and their components [muscle, fin, and blood separated into plasma and red blood cells (RBC)] were non-lethally extracted from three species of mesopredatory elasmobranchs and subjected to one of three treatment methods: (1) deionized water rinse [DW], (2) chloroform/methanol lipid extraction [LE], or (3) deionized water followed by chloroform/methanol [DW+LE]. In muscle δ 13 C, all treatments displayed minimal variation (∼ 0‰) but large increases in δ 15 N (∼ 1‰) indicated urea removal. Fin δ 13 C values decreased with DW but increased with LE and DW+LE, whilst all treatments increased fin δ 15 N (∼ 0.5‰), suggesting removal of both lipid and urea. Plasma δ 13 C and δ 15 N displayed high individual variation; large decreases in δ 13 C (∼−0.8‰) across all treatments, but particularly DW, suggested the removal of 13 C-enriched compounds while a small increase in δ 15 N (∼ 0.2‰) suggested minimal urea removal. In RBC, all treatments showed small δ 13 C declines (∼−0.5‰), with no difference in δ 15 N, suggesting minimal removal of 13 C-enriched compounds and urea. For muscle and fin, DW+LE is the most appropriate treatment to standardize δ 13 C and δ 15 N consistently across individuals and tissues. The large individual variation in treatment effects on plasma suggests it is unsuitable for current treatment methods. Consistent treatment effects for RBC allow for DW+LE standardization, however, broader species-specific effects are unknown. The importance of treatment choice for accurately estimating prey contributions to elasmobranch diet was highlighted using Bayesian stable isotope mixing model comparisons, with prey contributions varying significantly among treatments. This variability suggests that ecological inferences from elasmobranch tissue SIA are not robust to different treatment methods. It is recommended that studies employ standardized corrections using a combined DW+LE treatment where applicable.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Genome-wide analysis of mitochondrial DNA copy number reveals loci implicated in nucleotide metabolism, platelet activation, and megakaryocyte proliferation - R. J. Longchamps; S. Y. Yang; C. A. Castellani; W. Shi; J. Lane; M. L. Grove; T. M. Bartz; C. Sarnowski; C. Liu; K. Burrows; A. L. Guyatt; T. R. Gaunt; et al. (Human Genetics, 2022)
Mitochondrial DNA copy number (mtDNA-CN) measured from blood specimens is a minimally invasive marker of mitochondrial function that exhibits both inter-individual and intercellular variation. To identify genes involved in regulating mitochondrial function, we performed a genome-wide association study (GWAS) in 465,809 White individuals from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank (UKB). We identified 133 SNPs with statistically significant, independent effects associated with mtDNA-CN across 100 loci. A combination of fine-mapping, variant annotation, and co-localization analyses was used to prioritize genes within each of the 133 independent sites. Putative causal genes were enriched for known mitochondrial DNA depletion syndromes ( p = 3.09 × 10 –15 ) and the gene ontology (GO) terms for mtDNA metabolism ( p = 1.43 × 10 –8 ) and mtDNA replication ( p = 1.2 × 10 –7 ). A clustering approach leveraged pleiotropy between mtDNA-CN associated SNPs and 41 mtDNA-CN associated phenotypes to identify functional domains, revealing three distinct groups, including platelet activation, megakaryocyte proliferation, and mtDNA metabolism. Finally, using mitochondrial SNPs, we establish causal relationships between mitochondrial function and a variety of blood cell-related traits, kidney function, liver function and overall ( p = 0.044) and non-cancer mortality ( p = 6.56 × 10 –4 ).

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Application of DNA mini-barcoding reveals illegal trade in endangered shark products in southern Africa - TA Asbury; R Bennett; AS Price; C da Silva; M Bürgener; JD Klein; SN Maduna; N Sidat; S Fernando; AE Bester-van der Merwe (African Journal of Marine Science, 2021)

Come together: calibration of tiger shark (Galeocerdo cuvier) microsatellite databases for investigating global population structure and assignment of historical specimens - M. Sort; A. Manuzzi; B. Jiménez-Mena; J. R. Ovenden; B. J. Holmes; A. M. Bernard; M. S. Shivji; D. Meldrup; M. B. Bennett; E. E. Nielsen (Conservation Genetics Resources, 2021)

A global collaboration to study intimate partner violence-related head trauma: The ENIGMA consortium IPV working group - Carrie Esopenko; Jessica Meyer; Elisabeth A. Wilde; Amy D. Marshall; David F. Tate; Alexander P. Lin; Inga K. Koerte; Kimberly B. Werner; Emily L. Dennis; Ashley L. Ware; Nicola L. de Souza; Deleene S. Menefee; et al. (Brain Imaging and Behavior, 2021)

Central adiposity at diagnosis may reduce prostate cancer-specific mortality in African-Caribbean men with prostate cancer: 10-year follow-up of participants in a case–control study - Maria D. Jackson; Marshall K. Tulloch-Reid; Affette M. McCaw-Binns; William Aiken; Trevor S. Ferguson; Nadia R. Bennett; Leroy Harrison; Asha Badaloo; Donovan McGrowder; Annielle Grindley; Evelyn Walker; Simon G. Anderson (Cancer Causes & Control, 2020)

Climate and local environment structure asynchrony and the stability of primary production in grasslands - Benjamin Gilbert; Andrew S. MacDougall; Taku Kadoya; Munemitsu Akasaka; Joseph R. Bennett; Eric M. Lind; Habacuc Flores‐Moreno; Jennifer Firn; Yann Hautier; Elizabeth T. Borer; Eric W. Seabloom; Peter B. Adler; et al. (Global Ecology and Biogeography, 2020)
Aim Climate variability threatens to destabilize production in many ecosystems. Asynchronous species dynamics may buffer against such variability when a decrease in performance by some species is offset by an increase in performance of others. However, high climatic variability can eliminate species through stochastic extinctions or cause similar stress responses among species that reduce buffering. Local conditions, such as soil nutrients, can also alter production stability directly or by influencing asynchrony. We test these hypotheses using a globally distributed sampling experiment. Location Grasslands in North America, Europe and Australia. Time period Annual surveys over 5 year intervals occurring between 2007 and 2014. Major taxa studied Herbaceous plants. Methods We sampled annually the per species cover and aboveground community biomass [net primary productivity (NPP)], plus soil chemical properties, in 29 grasslands. We tested how soil conditions, combined with variability in precipitation and temperature, affect species richness, asynchrony and temporal stability of primary productivity. We used bivariate relationships and structural equation modelling to examine proximate and ultimate relationships. Results Climate variability strongly predicted asynchrony, whereas NPP stability was more related to soil conditions. Species richness was structured by both climate variability and soils and, in turn, increased asynchrony. Variability in temperature and precipitation caused a unimodal asynchrony response, with asynchrony being lowest at low and high climate variability. Climate impacted stability indirectly, through its effect on asynchrony, with stability increasing at higher asynchrony owing to lower inter‐annual variability in NPP. Soil conditions had no detectable effect on asynchrony but increased stability by increasing the mean NPP, especially when soil organic matter was high. Main conclusions We found globally consistent evidence that climate modulates species asynchrony but that the direct effect on stability is low relative to local soil conditions. Nonetheless, our observed unimodal responses to variability in temperature and precipitation suggest asynchrony thresholds, beyond which there are detectable destabilizing impacts of climate on primary productivity.

Patient- and area-level predictors of prostate cancer among South Carolina veterans: a spatial analysis - Peter Georgantopoulos; Jan M. Eberth; Bo Cai; Christopher Emrich; Gowtham Rao; Charles L. Bennett; Kathlyn S. Haddock; James R. Hébert (Cancer Causes & Control, 2020)

Homogenization of freshwater lakes: Recent compositional shifts in fish communities are explained by gamefish movement and not climate change - Kevin Cazelles; Timothy Bartley; Matthew M. Guzzo; Marie‐Hélène Brice; Andrew S. MacDougall; Joseph R. Bennett; Ellen H. Esch; Taku Kadoya; Jocelyn Kelly; Shin‐ichiro Matsuzaki; Karin A. Nilsson; Kevin S. McCann (Global Change Biology, 2019)
Globally, lake fish communities are being subjected to a range of scale‐dependent anthropogenic pressures, from climate change to eutrophication, and from overexploitation to species introductions. As a consequence, the composition of these communities is being reshuffled, in most cases leading to a surge in taxonomic similarity at the regional scale termed homogenization. The drivers of homogenization remain unclear, which may be a reflection of interactions between various environmental changes. In this study, we investigate two potential drivers of the recent changes in the composition of freshwater fish communities: recreational fishing and climate change. Our results, derived from 524 lakes of Ontario, Canada sampled in two periods (1965–1982 and 2008–2012), demonstrate that the main contributors to homogenization are the dispersal of gamefish species, most of which are large predators. Alternative explanations relating to lake habitat (e.g., area, phosphorus) or variations in climate have limited explanatory power. Our analysis suggests that human‐assisted migration is the primary driver of the observed compositional shifts, homogenizing freshwater fish community among Ontario lakes and generating food webs dominated by gamefish species.

Integrated Risk Assessment for the Blue Economy - Emma E. Hodgson; Timothy E. Essington; Jameal F. Samhouri; Edward H. Allison; Nathan J. Bennett; Ann Bostrom; Alison C. Cullen; Stephen Kasperski; Phillip S. Levin; Melissa R. Poe (Frontiers in Marine Science, 2019)

Sex Differences in Gene and Protein Expression After Intracerebral Hemorrhage in Mice - Yongqiu Xie; Yi-Ju Li; Beilei Lei; Dawn Kernagis; Wen-Wei Liu; Ellen R. Bennett; Talagnair Venkatraman; Christopher D. Lascola; Daniel T. Laskowitz; David S. Warner; Michael L. James (Translational Stroke Research, 2019)

Watershed Buffering of Legacy Phosphorus Pressure at a Regional Scale: A Comparison Across Space and Time - A. S. Kusmer; J.-O. Goyette; G. K. MacDonald; E. M. Bennett; R. Maranger; P. J. A. Withers (Ecosystems, 2019)

Research Priorities to Support Effective Manta and Devil Ray Conservation - Joshua D. Stewart; Fabrice R. A. Jaine; Amelia J. Armstrong; Asia O. Armstrong; Michael B. Bennett; Katherine B. Burgess; Lydie I. E. Couturier; Donald A. Croll; Melissa R. Cronin; Mark H. Deakos; Christine L. Dudgeon; Daniel Fernando; et al. (Frontiers in Marine Science, 2018)

Climate change alterations to ecosystem dominance: how might sponge‐dominated reefs function? - James J. Bell; Alberto Rovellini; Simon K. Davy; Michael W. Taylor; Elizabeth A. Fulton; Matthew R. Dunn; Holly M. Bennett; Nora M. Kandler; Heidi M. Luter; Nicole S. Webster (Ecology, 2018)
Anthropogenic stressors are impacting ecological systems across the world. Of particular concern are the recent rapid changes occurring in coral reef systems. With ongoing degradation from both local and global stressors, future reefs are likely to function differently from current coral‐dominated ecosystems. Determining key attributes of future reef states is critical to reliably predict outcomes for ecosystem service provision. Here we explore the impacts of changing sponge dominance on coral reefs. Qualitative modelling of reef futures suggests that changing sponge dominance due to increased sponge abundance will have different outcomes for other trophic levels compared with increased sponge dominance as a result of declining coral abundance. By exploring uncertainty in the model outcomes we identify the need to (1) quantify changes in carbon flow through sponges, (2) determine the importance of food limitation for sponges, (3) assess the ubiquity of the recently described “sponge loop,” (4) determine the competitive relationships between sponges and other benthic taxa, particularly algae, and (5) understand how changing dominance of other organisms alters trophic pathways and energy flows through ecosystems. Addressing these knowledge gaps will facilitate development of more complex models that assess functional attributes of sponge‐dominated reef ecosystems.

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Genome-Wide Association Analysis of the Sense of Smell in U.S. Older Adults: Identification of Novel Risk Loci in African-Americans and European-Americans - Jing Dong; Annah Wyss; Jingyun Yang; T. Ryan Price; Aude Nicolas; Michael Nalls; Greg Tranah; Nora Franceschini; Zongli Xu; Claudia Schulte; Alvaro Alonso; Steven R. Cummings; et al. (Molecular Neurobiology, 2017)

Pineal volume and evening melatonin in young people with affective disorders - Joanne S. Carpenter; Amy C. Abelmann; Sean N. Hatton; Rébecca Robillard; Daniel F. Hermens; Maxwell R. Bennett; Jim Lagopoulos; Ian B. Hickie (Brain Imaging and Behavior, 2017)

Angling into the Future: Ten Commandments for Recreational Fisheries Science, Management, and Stewardship in a Good Anthropocene - Laura K. Elmer; Lisa A. Kelly; Stephanie Rivest; S. Clay Steell; William M. Twardek; Andy J. Danylchuk; Robert Arlinghaus; Joseph R. Bennett; Steven J. Cooke (Environmental Management, 2017)

Balancing generality and specificity in ecological gradient analysis with species abundance distributions and individual size distributions - Jian D. L. Yen; James R. Thomson; Jonathan M. Keith; David M. Paganin; Erica Fleishman; David S. Dobkin; Joanne M. Bennett; Ralph Mac Nally (Global Ecology and Biogeography, 2017)
Aim Data on ecological communities are often condensed into single‐valued diversity indices, which support comparisons among ecosystems but may discard important information. At the other extreme, some studies retain full data on the identities of all species present, which retains maximum information on community structure but occludes comparisons among ecosystems. We sought to determine whether the analysis of species abundance distributions and individual size distributions could support more detailed inferences than diversity indices while remaining sufficiently general to identify fundamental ecological responses in multiple ecosystems. Location The United States and south‐eastern Australia. Methods We analysed changes in species abundance distributions and individual size distributions along environmental gradients. We compared analyses of distributions with analyses of five diversity indices and with a distance‐based multivariate analysis of species composition. We used data from 1438 fish communities in the United States and from 840 bird communities in the western United States and south‐eastern Australia. These communities were sampled over 10–20 years and included 298 species of birds and 488 species of fishes. Results Analyses of species abundance distributions and individual size distributions identified environmental associations that were not found in analyses of diversity indices, and revealed common associations with shrubs in bird communities on different continents and with temperature in communities of birds and fishes. Individual size distributions were associated more closely with environmental variables than were species abundance distributions. Main conclusions Our novel identification of ecological associations suggests that analyses of community distributions might reveal fundamental ecological processes common to multiple ecosystems. Close associations between individual sizes and environmental variables suggest that a greater focus on size in ecological analyses might assist in the development of general models of ecological communities.

Community assembly on isolated islands: macroecology meets evolution - A. J. Rominger; K. R. Goodman; J. Y. Lim; E. E. Armstrong; L. E. Becking; G. M Bennett; M. S. Brewer; D. D. Cotoras; C. P. Ewing; J. Harte; N. D. Martinez; P. M. O'Grady; et al. (Global Ecology and Biogeography, 2016)
Aim Understanding how ecological and evolutionary processes together determine patterns of biodiversity remains a central aim in biology. Guided by ecological theory, we use data from multiple arthropod lineages across the Hawaiian archipelago to explore the interplay between ecological (population dynamics, dispersal, trophic interactions) and evolutionary (genetic structuring, adaptation, speciation, extinction) processes. Our goal is to show how communities develop from the dynamic feedbacks that operate at different temporal and spatial scales. Location The Hawaiian islands (19–22° N , 155–160° W ). Methods We synthesize genetic data from selected arthropods across the Hawaiian archipelago to determine the relative role of dispersal and in situ differentiation across the island chronosequence. From four sites on three high islands with geological ages ranging from Results From the perspective of the island chronosequence we show that species at lower trophic levels develop population genetic structure at smaller temporal and spatial scales than species at higher trophic levels. Network nestedness decreases while modularity increases with habitat age. Single‐island endemics exhibit more specialization than broadly distributed species, but both show the least specialization in communities on middle‐aged substrates. Plant–herbivore networks also show the least deviation from theoretical predictions in middle‐aged communities. Main conclusions The application of ecological theory to island chronosequences can illuminate feedbacks between ecological and evolutionary processes in community assembly. We show how patterns of population genetic structure, decreasing network nestedness, increasing network modularity and increased specialization shift from early assembly driven by immigration, to in situ diversification after > 1 Myr. Herbivore–plant communities only transiently achieve statistical steady state during assembly, presumably due to incomplete assembly from dispersal in the early stages, and the increasing influence of island ontogeny on older islands.

Unpacking Pandora’s Box: Understanding and Categorising Ecosystem Disservices for Environmental Management and Human Wellbeing - C. M. Shackleton; S. Ruwanza; G. K. Sinasson Sanni; S. Bennett; P. De Lacy; R. Modipa; N. Mtati; M. Sachikonye; G. Thondhlana (Ecosystems, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Anthropogenic‐based regional‐scale factors most consistently explain plot‐level exotic diversity in grasslands - Andrew S. MacDougall; Joseph R. Bennett; Jennifer Firn; Eric W. Seabloom; Elizabeth T. Borer; Eric M. Lind; John L. Orrock; W. Stanley Harpole; Yann Hautier; Peter B. Adler; Elsa Cleland; Kendi Davies; et al. (Global Ecology and Biogeography, 2014)
Aim Evidence linking the accumulation of exotic species to the suppression of native diversity is equivocal, often relying on data from studies that have used different methods. Plot‐level studies often attribute inverse relationships between native and exotic diversity to competition, but regional abiotic filters, including anthropogenic influences, can produce similar patterns. We seek to test these alternatives using identical scale‐dependent sampling protocols in multiple grasslands on two continents. Location Thirty‐two grassland sites in N orth A merica and A ustralia. Methods We use multiscale observational data, collected identically in grain and extent at each site, to test the association of local and regional factors with the plot‐level richness and abundance of native and exotic plants. Sites captured environmental and anthropogenic gradients including land‐use intensity, human population density, light and soil resources, climate and elevation. Site selection occurred independently of exotic diversity, meaning that the numbers of exotic species varied randomly thereby reducing potential biases if only highly invaded sites were chosen. Results Regional factors associated directly or indirectly with human activity had the strongest associations with plot‐level diversity. These regional drivers had divergent effects: urban‐based economic activity was associated with high exotic : native diversity ratios; climate‐ and landscape‐based indicators of lower human population density were associated with low exotic : native ratios. Negative correlations between plot‐level native and exotic diversity, a potential signature of competitive interactions, were not prevalent; this result did not change along gradients of productivity or heterogeneity. Main conclusion We show that plot‐level diversity of native and exotic plants are more consistently associated with regional‐scale factors relating to urbanization and climate suitability than measures indicative of competition. These findings clarify the long‐standing difficulty in resolving drivers of exotic diversity using single‐factor mechanisms, suggesting that multiple interacting anthropogenic‐based processes best explain the accumulation of exotic diversity in modern landscapes.

Population dynamics of the reef manta ray Manta alfredi in eastern Australia - L. I. E. Couturier; C. L. Dudgeon; K. H. Pollock; F. R. A. Jaine; M. B. Bennett; K. A. Townsend; S. J. Weeks; A. J. Richardson (Coral Reefs, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Stress-Induced Grey Matter Loss Determined by MRI Is Primarily Due to Loss of Dendrites and Their Synapses - Mustafa S. Kassem; Jim Lagopoulos; Tim Stait-Gardner; William S. Price; Tariq W. Chohan; Jonathon C. Arnold; Sean N. Hatton; Maxwell R. Bennett (Molecular Neurobiology, 2013)

Complete genome sequence of arracacha virus B: a novel cheravirus - I. P. Adams; R. Glover; R. Souza-Richards; S. Bennett; U. Hany; N. Boonham (Archives of Virology, 2013)

Fire Mosaics and Reptile Conservation in a Fire‐Prone Region - D. G. NIMMO; L. T. KELLY; L. M. SPENCE‐BAILEY; S. J. WATSON; R. S. TAYLOR; M. F. CLARKE; A. F. BENNETT (Conservation Biology, 2013)
Fire influences the distribution of fauna in terrestrial biomes throughout the world. Use of fire to achieve a mosaic of vegetation in different stages of succession after burning (i.e., patch‐mosaic burning) is a dominant conservation practice in many regions. Despite this, knowledge of how the spatial attributes of vegetation mosaics created by fire affect fauna is extremely scarce, and it is unclear what kind of mosaic land managers should aim to achieve. We selected 28 landscapes (each 12.6 km 2 ) that varied in the spatial extent and diversity of vegetation succession after fire in a 104,000 km 2 area in the semiarid region of southeastern Australia. We surveyed for reptiles at 280 sites nested within the 28 landscapes. The landscape‐level occurrence of 9 of the 22 species modeled was associated with the spatial extent of vegetation age classes created by fire. Biogeographic context and the extent of a vegetation type influenced 7 and 4 species, respectively. No species were associated with the diversity of vegetation ages within a landscape. Negative relations between reptile occurrence and both extent of recently burned vegetation (≤10 years postfire, n = 6) and long unburned vegetation (>35 years postfire, n = 4) suggested that a coarse‐grained mosaic of areas (e.g. >1000 ha) of midsuccessional vegetation (11–35 years postfire) may support the fire‐sensitive reptile species we modeled. This age class coincides with a peak in spinifex cover, a keystone structure for reptiles in semiarid and arid Australia. Maintaining over the long term a coarse‐grained mosaic of large areas of midsuccessional vegetation in mallee ecosystems will need to be balanced against the short‐term negative effects of large fires on many reptile species and a documented preference by species from other taxonomic groups, particularly birds, for older vegetation. Mosaicos de Fuego y la Conservación de Reptiles en una Región Propensa al Fuego

Hybrid mouse diversity panel: a panel of inbred mouse strains suitable for analysis of complex genetic traits - Anatole Ghazalpour; Christoph D. Rau; Charles R. Farber; Brian J. Bennett; Luz D. Orozco; Atila van Nas; Calvin Pan; Hooman Allayee; Simon W. Beaven; Mete Civelek; Richard C. Davis; Thomas A. Drake; et al. (Mammalian Genome, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Biology, ecology and conservation of the Mobulidae - L. I. E. Couturier; A. D. Marshall; F. R. A. Jaine; T. Kashiwagi; S. J. Pierce; K. A. Townsend; S. J. Weeks; M. B. Bennett; A. J. Richardson (Journal of Fish Biology, 2012)
The Mobulidae are zooplanktivorous elasmobranchs comprising two recognized species of manta rays ( Manta spp.) and nine recognized species of devil rays ( Mobula spp.). They are found circumglobally in tropical, subtropical and temperate coastal waters. Although mobulids have been recorded for over 400 years, critical knowledge gaps still compromise the ability to assess the status of these species. On the basis of a review of 263 publications, a comparative synthesis of the biology and ecology of mobulids was conducted to examine their evolution, taxonomy, distribution, population trends, movements and aggregation, reproduction, growth and longevity, feeding, natural mortality and direct and indirect anthropogenic threats. There has been a marked increase in the number of published studies on mobulids since c . 1990, particularly for the genus Manta , although the genus Mobula remains poorly understood. Mobulid species have many common biological characteristics although their ecologies appear to be species‐specific, and sometimes region‐specific. Movement studies suggest that mobulids are highly mobile and have the potential to rapidly travel large distances. Fishing pressure is the major threat to many mobulid populations, with current levels of exploitation in target fisheries unlikely to be sustainable. Advances in the fields of population genetics, acoustic and satellite tracking, and stable‐isotope and fatty‐acid analyses will provide new insights into the biology and ecology of these species. Future research should focus on the uncertain taxonomy of mobulid species, the degree of overlap between their large‐scale movement and human activities such as fisheries and pollution, and the need for management of inter‐jurisdictional fisheries in developing nations to ensure their long‐term sustainability. Closer collaboration among researchers worldwide is necessary to ensure standardized sampling and modelling methodologies to underpin global population estimates and status.

Differences in NMDA Receptor Expression During Human Development Determine the Response of Neurons to HIV-Tat-mediated Neurotoxicity - E. A. Eugenin; J. E. King; J. E. Hazleton; E. O. Major; M. V. L. Bennett; R. S. Zukin; Joan W. Berman (Neurotoxicity Research, 2011)

Association of common DNA sequence variants at 33 genetic loci with blood lipids in individuals of African ancestry from Jamaica - R. Gupta; K. Ejebe; J. Butler; G. Lettre; H. Lyon; C. Guiducci; R. Wilks; F. Bennett; T. Forrester; B. Tayo; K. Musunuru; J. Hirschhorn; et al. (Human Genetics, 2010)

Branching coral as a macroalgal refuge in a marginal coral reef system - S. Bennett; A. Vergés; D. R. Bellwood (Coral Reefs, 2010)

Composition and location of simulated lake‐shore redds influence incubation success in kokanee, Oncorhynchus nerka - M. J. FINCEL; S. R. CHIPPS; D. H. BENNETT (Fisheries Management and Ecology, 2009)
Methods for improving spawning habitat for lakeshore spawning kokanee, Oncorhynchus nerka (Walbaum), were explored by quantifying incubation success of embryos exposed to three substrate treatments in Lake Pend Oreille, Idaho, USA. Substrate treatments included no modification that used existing gravels in the lake (EXISTING), a cleaned substrate treatment where existing gravels were sifted in the water column to remove silt (CLEANED) and the addition of new, silt‐free gravel (ADDED). Incubation success was evaluated using Whitlock–Vibert incubation boxes buried within each substrate treatment that contained recently fertilised embryos. Upon retrieval, live and dead sac fry and eyed eggs were enumerated to determine incubation success (sac fry and eyed eggs × 100/number of fertilised embryos). Incubation success varied significantly among locations and redd treatments. In general, incubation success among ADDED redds (0.0–13.0%) was significantly lower than that for EXISTING (1.4–61.0%) and CLEANED (0.4–62.5%) redds. Adding new gravel to spawning areas changed the morphometry of the gravel‐water interface and probably exposed embryos to disturbance from wave action and reduced embryo survival. Moreover, efforts to improve spawning habitat for lakeshore spawning kokanee should consider water depth and location (e.g. protected shorelines) as important variables. Adding clean gravel to existing spawning areas may provide little benefit if water depth or lake‐bottom morphometry are altered.

Diazinon Mitigation in Constructed Wetlands: Influence of Vegetation - M. T. Moore; C. M. Cooper; S. Smith; R. F. Cullum; S. S. Knight; M. A. Locke; E. R. Bennett (Water, Air, & Soil Pollution, 2007)

Tissue-Specific Expression and Drought Responsiveness of Cell-Wall Invertase Genes of Rice at Flowering - X. M. Ji; M. Raveendran; R. Oane; A. Ismail; R. Lafitte; R. Bruskiewich; S. H. Cheng; J. Bennett (Plant Molecular Biology, 2005)

Case Study Part 2: Probabilistic Modelling of Long-term Effects of Pesticides on Individual Breeding Success in Birds and Mammals - W. ROELOFS; D.R. CROCKER; R.F. SHORE; D.R.J. MOORE; G.C. SMITH; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; et al. (Ecotoxicology, 2005)

Case Study Part 1: How to Calculate Appropriate Deterministic Long-Term Toxicity to Exposure Ratios (TERs) for Birds and Mammals - R.F. SHORE; D.R. CROCKER; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; A. FAIRBROTHER; S. FERSON; D. FISCHER; et al. (Ecotoxicology, 2005)

Identification of flanking SSR markers for a major rice gall midge resistance gene Gm1 and their validation - S. K. Biradar; R. M. Sundaram; T. Thirumurugan; J. S. Bentur; S. Amudhan; V. V. Shenoy; B. Mishra; J. Bennett; N. P. Sarma (Theoretical and Applied Genetics, 2004)

Acute Toxicity of Methyl-Parathion in Wetland Mesocosms: Assessing the Influence of Aquatic Plants Using Laboratory Testing with Hyalella azteca - R. Schulz; M. T. Moore; E. R. Bennett; C. D. Milam; J. L. Bouldin; J. L. Farris; S. Smith; C. M. Cooper (Archives of Environmental Contamination and Toxicology, 2003)

Biodiversity and biogeography of the islands of the Kuril Archipelago - Theodore W. Pietsch; Victor V. Bogatov; Kunio Amaoka; Yuri N. Zhuravlev; Vyacheslav Y. Barkalov; Sarah Gage; Hideki Takahashi; Arkady S. Lelej; Sergey Y. Storozhenko; Norobu Minakawa; Daniel J. Bennett; Trevor R. Anderson; et al. (Journal of Biogeography, 2003)
Aim Based on seven consecutive seasons of biotic survey and inventory of the terrestrial and freshwater plants and animals of the 30 major islands of the Kuril Archipelago, a description of the biodiversity and an analysis of the biogeography of this previously little known part of the world are provided. Location The Kuril Archipelago, a natural laboratory for investigations into the origin, subsequent evolution, and long‐term maintenance of insular populations, forms the eastern boundary of the Okhotsk Sea, extending 1200 km between Hokkaido, Japan, and the Kamchatka Peninsula of Russia. A chain of more than 56 islands, the system is only slightly smaller than the Hawaiian Islands, covering an area of 15,600 km 2 and providing 2409 km of coastline. Methods Collections of whole specimens of plants and animals, as well as tissue samples for future molecular studies, were made by teams of scientists from Russia, Japan, and the USA, averaging 34 people for each of the seven annual summer expeditions (1994–2000). Floral and faunal similarities between islands were evaluated by using Sorensen's coefficient of similarity. The similarity matrix resulting from pair‐wise calculations was then subjected to UPGMA cluster analysis. Results Despite the relatively small geographical area of all islands combined, the Kuril Island biota is characterized by unusually high taxonomic diversity, yet endemism is very low. An example of a non‐relict biota, it originated from two primary sources: a southern source, the Asian mainland by way of Sakhalin and Hokkaido, and a northern source by way of Kamchatka. The contribution of the southern source biota to the species diversity of the Kurils was considerably greater than the northern one. Main conclusion The Bussol Strait, lying between Urup and Simushir in the central Kurils, is the most significant biogeographical boundary within the Archipelago. Of lesser importance are two transitional zones, the De Vries Strait or ‘Miyabe Line’, which passes between Iturup and Urup in the southern Kurils, and the fourth Kuril Strait, between Onekotan and Paramushir in the northern Kurils.

[3H]-thymidine labelling of DNA triggers apoptosis potentiated by E1A-adenoviral protein - S. N. Orlov; D. V. Pchejetski; S. Der Sarkissian; V. Adarichev; S. Taurin; A. V. Pshezhetsky; J. Tremblay; G. V. Maximov; D. deBlois; M. R. Bennett; P. Hamet (Apoptosis, 2003)

Molecular systematics of Solanum section Lycopersicum (Lycopersicon) using the nuclear ITS rDNA region - J. A. Marshall; S. Knapp; M. R. Davey; J. B. Power; E. C. Cocking; M. D. Bennett; A. V. Cox (Theoretical and Applied Genetics, 2001)

Method for the Simultaneous Extraction and Analysis of Two Current Use Pesticides, Atrazine and Lambda-Cyhalothrin, in Sediment and Aquatic Plants - E. R. Bennett; M. T. Moore; C. M. Cooper; S. Smith Jr. (Bulletin of Environmental Contamination and Toxicology, 2000)

Method for the Simultaneous Extraction and Analysis of Two Current Use Pesticides, Atrazine and Lambda-Cyhalothrin, in Sediment and Aquatic Plants - E. R. Bennett; M. T. Moore; C. M. Cooper; S. Smith (Bulletin of Environmental Contamination and Toxicology, 2000)

Molecular cloning of transmembrane and soluble forms of a novel rat natural killer cell receptor related to 2B4 - P. R. Kumaresan; S. E. Stepp; M. Bennett; V. Kumar; P. A. Mathew (Immunogenetics, 2000)

Interactive effects of subanesthetic ketamine and haloperidol in healthy humans - John H. Krystal; D. Cyril D'Souza; Laurence P. Karper; Alexandre Bennett; Anissa Abi-Dargham; Danielle Abi-Saab; Karyn Cassello; M. B. Bowers Jr.; Sally Vegso; George R. Heninger; Dennis S. Charney; M. B. Bowers (Psychopharmacology, 1999)

The reach-to-grasp movement in Parkinson's disease: response to a simultaneous perturbation of object position and object size - U. Castiello; K. Bennett; C. Bonfiglioli; S. Lim; R. F. Peppard (Experimental Brain Research, 1999)

Subacute and Reproductive Effects in Mink from Exposure to Fusarium fujikuroi Culture Material (M-1214) Containing Known Concentrations of Moniliformin - M. K. Morgan; S. J. Bursian; G. E. Rottinghaus; G. A. Bennett; J. A. Render; R. J. Aulerich (Archives of Environmental Contamination and Toxicology, 1998)

Interactive effects of subanesthetic ketamine and subhypnotic lorazepam in humans - John H. Krystal; Laurence P. Karper; Alexandre Bennett; D. Cyril D'Souza; Anissa Abi-Dargham; Kristen Morrissey; Danielle Abi-Saab; J. Douglas Bremner; M. B. Bowers Jr.; Raymond F. Suckow; Philip Stetson; George R. Heninger; et al. (Psychopharmacology, 1998)

The Cystatin S gene maps to rat Chromosome 3, to which Dlmgh18 is re-assigned from Chromosome 1 - M. Beatriz Duran Alonso; Paul Shiels; Andrew S. McCallion; Neil K. Bennett; Anthony P. Payne; Josiane Szpirer; Claude Szpirer; Martin J. Brodie; R. Wayne Davies; Roger G. Sutciffe (Mammalian Genome, 1997)

Pyramiding of bacterial blight resistance genes in rice: marker-assisted selection using RFLP and PCR - N. Huang; E. R. Angeles; J. Domingo; G. Magpantay; S. Singh; G. Zhang; N. Kumaravadivel; J. Bennett; G. S. Khush (Theoretical and Applied Genetics, 1997)

Homoeologous pairing and recombination in backcross derivatives of tomato somatic hybrids [Lycopersicon esculentum (+) L. peruvianum] - A. S. Parokonny; J. A. Marshall; M. D. Bennett; E. C. Cocking; M. R. Davey; J. Brian Power (Theoretical and Applied Genetics, 1997)

Zipping up transcription factors: Rational design of anti-Jun and anti-Fos peptides - Naresh P. S. Bains; Jackie A. Wilce; Katja H. Heuer; Mark Tunstall; Joel P. Mackey; Max R. Bennett; Anthony S. Weiss; Glenn F. King (International Journal of Peptide Research and Therapeutics, 1997)

Perceptions of Species Abundance, Distribution, and Diversity: Lessons from Four Decades of Sampling on a Government-Managed Reserve - J. Whitfield Gibbons; Vincent J. Burke; Jeffrey E. Lovich; Raymond D. Semlitsch; Tracey D. Tuberville; J. Russell Bodie; Judith L. Greene; Peter H. Niewiarowski; Howard H. Whiteman; David E. Scott; Joseph H. K. Pechmann; Christopher R. Harrison; et al. (Environmental Management, 1997)

An interpretation of toxicity response of bobwhite quail with respect to duration of exposure - M. A. Shirazi; R. S. Bennett; R. K. Ringer (Archives of Environmental Contamination and Toxicology, 1994)

Latency and reactivation of infectious laryngotracheitis vaccine virus - C. S. Hughes; R. A. Williams; R. M. Gaskell; F. T. W. Jordan; J. M. Bradbury; M. Bennett; R. C. Jones (Archives of Virology, 1991)

Sectional notes - M. A. Lindsay; E. Marx; E. R. Bennett; C. L. Fitch; A. A. Henderson; Mitchell Jenkins; G. S. Ralston (American Journal of Potato Research, 1941)

Sectional notes - C. H. Metzger; E. R. Bennett; W. B. Ward; J. G. Richard; Ralph W. Donaldson; T. M. Patterson; L. Harris; Marx Koehnke; J. M. Jenkins; W. H. Martin; Robert Schmidt; E. M. Gillig; et al. (American Journal of Potato Research, 1937)

Sectional notes - H. G. Zuckerman; C. H. Metzger; E. R. Bennett; W. B. Ward; A. G. Tolaas; Ralph W. Donaldson; E. V. Hardenburg; K. W. Lauer; H. L. Bailey; G. S. Ralston; John Tucker (American Journal of Potato Research, 1936)

Sectional notes - E. R. Bennett; W. B. Ward; C. L. Fitch; Frank W. Hussey; H. R. Talmage; Ralph W. Donaldson; Marx Koehnke; Wm. H. Martin; J. B. R. Dickey; K. H. Klages; G. S. Ralston (American Journal of Potato Research, 1935)

Sectional notes - J. H. Heckman; H. G. Zuckerman; C. H. Metzger; B. A. Brown; E. R. Bennett; W. B. Ward; C. L. Fitch; O. H. Elmer; Jhon S. Gardner; Julan C. Miller; Frank W. Hussey; E. L. Newdick; et al. (American Journal of Potato Research, 1935)

Sectional notes - E. R. Bennett; W. B. Ward; John S. Gardner; Dudley Bagley; J. R. Livermore; E. B. Tussing; J. G. Milward; J. Tucker (American Journal of Potato Research, 1934)

Sectional notes - H. G. Zuckerman; C. H. Metzger; E. R. Bennett; W. B. Ward; John S. Gardner; E. L. Newdick; Ralph W. Donaldson; H. C. Moore; E. E. Isaac; William H. Martin; J. R. Livermore; Karl H. Fernow; et al. (American Journal of Potato Research, 1934)